1998
DOI: 10.1073/pnas.95.4.1613
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of inositol 1,4,5-trisphosphate-induced Ca 2+ release by cAMP-dependent protein kinase in a living cell

Abstract: Interaction of intracellular free calcium ([Ca 2؉ ] i ) and cAMP signaling mechanisms was examined in intact single megakaryocytes by using a combination of singlecell f luorescence microscopy to measure [Ca 2؉ ] i and f lash photolysis of caged Ca 2؉ , inositol 1,4,5-trisphosphate (IP 3 ), or cAMP to elevate rapidly the concentration of these compounds inside the cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 55 publications
(56 reference statements)
5
60
1
Order By: Relevance
“…Opening of IP3R-operated stores and activation of TRPC1 and voltage-gated channels result in an increase of Ca 2+ spike activity. Activated Smo also inhibits PKA, which can inhibit IP3-induced Ca 2+ release (43). Hence, modulation of Ca 2+ spike activity may occur by pathways that are parallel or convergent to the one operated by PLC.…”
Section: Discussionmentioning
confidence: 99%
“…Opening of IP3R-operated stores and activation of TRPC1 and voltage-gated channels result in an increase of Ca 2+ spike activity. Activated Smo also inhibits PKA, which can inhibit IP3-induced Ca 2+ release (43). Hence, modulation of Ca 2+ spike activity may occur by pathways that are parallel or convergent to the one operated by PLC.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this effect, a number of studies have found that the inositol 1,4,5-trisphosphate (IP 3 ) receptor (IP 3 R) is phosphorylated by PKA, apparently resulting in reduced Ca 2+ release from the endoplasmic reticulum (ER) in response to IP 3 [121,122]. It is now known that there are at least three types of IP 3 R and that, in ASM, cAMP and cGMP both promote the PKG-dependent phosphorylation at Ser 1755 of the type 1 IP 3 R that predominates in this tissue [123].…”
Section: Modulation Of Cytosolic Free Calcium Concentrationmentioning
confidence: 87%
“…This indicates that the distinctive calcium response in MRL T cells upon CD3 engagement is not due to fuller stores or increased influx from the extracellular space following store depletion, but rather a result of prolonged activation of the InsP 3 receptor. Certain mechanisms have already been suggested to explain this early signaling defect in a variety of cell types, such as mitochondrial hyperpolarization with deficient calcium sequestration from the cytosol (61) or loss of protein kinase A I-mediated phospholipase C␥1 down-regulation with an increase in InsP 3 (62)(63)(64). The latter seems less plausible as a mechanism in MRL mice, as a similar percentage of T cells responded to anti-CD3 stimulation, which indicates that InsP 3 production is comparable.…”
Section: Discussionmentioning
confidence: 99%